Customer relationship management a business strategy - Tello Endara, Katherin (mktDESCUBRE, 2023)
The need to achieve competitiveness, development, profitability has generated that companies are more demanding with their internal processes, the research problem arises from the lack of communication with the customer which causes senior management to rethink its traditional processes and increase new technological tools that allow systematizing information and anticipating the needs and desires of customers in order to establish loyalty ties to customers. through technology in each of its processes. The present research uses a descriptive methodology through books and scientific articles that are primary sources, in which the application of a CRM in each of the stages of purchase of a product/service (pre-purchase, purchase, post-purchase) has been developed as a commercial strategy with the study of four phases: Phase I - Analysis of the company; Phase II - Strategy design; Phase III - Definition of built areas focused on marketing, sales and customer service departments; Phase IV - Implementation of CRM Software. The results showed that CRM facilitates customer attraction, loyalty, and retention, which, linked to the technological factor, optimizes processes, allowing data to be transformed into meaningful information for decision-making. As conclusions, it was identified that the application of a CRM improves customer relationship management, streamlines processes, increases profitability and provides a 360° long-term vision.